Предмет: Алгебра, автор: Аноним

Переобразуйте в многочлен. а) (a-b)(a+b)-(a-2b)². б) (x-4)(x+4)-(x+8)(x-8). Помогите пожалуйста !!​

Ответы

Автор ответа: SirWallon
0

Объяснение:

1)

(a - b)(a + b) -  {(a - 2b)}^{2}  =  {a}^{2}  -  {b}^{2}  -  {a}^{2}  + 4 {b}^{2}  = 3 {b}^{2}

2)

(x - 4)(x + 4) - (x + 8)(x - 8) =  {x}^{2}  - 16 -  {x}^{2}  + 64 = 48

Автор ответа: dratuti21
0
А) (a-b)(a+b)-(a-2b)^2= a^2-b^2-a^2+4ab-4b^2=4ab-5b^2

B)(x-4)(x+4)-(x+8)(x-8)= x^2-16-x^2+64 или 48
Похожие вопросы